PENGARUH EDUKASI KESEHATAN REPRODUKSI TERHADAP PENGETAHUAN SISWA/I TENTANG SEKS BEBAS DI SMKN 4 MERANGIN - Oktavianis Oktavianis; Ikhfa Istikomah (Maternal Child Health Care, 2021)
Free sex is one of the reproductive health problems in adolescents. The World Health Organization (2016) states that approximately 21 million young women aged 15–19 in developing countries experience pregnancy every year and nearly half of these pregnancies (49%) is an unwanted pregnancy. Such pregnancies are caused by deviant sex behaviors that tend to increase every year. This study aims to find out the effect of reproductive health education on students' knowledge about free sex at SMKN 4 Merangin in 2020.This research uses quantitative research design with pseudo pre-experimental method with one group pretest posttest design approach. This research was conducted on 01-10 December 2020 at SMKN 4 Merangin. The population in this study is all students of class X-XI SMKN 4 Merangin school year 2020/2021. Data collection using questionnaires. Data is analyzed univariately and bivariately.The results of this study showed that the average value of knowledge before education was 13.6849 and the average value of knowledge after being given education was 19,. There is an influence of reproductive health education on students' knowledge about free sex in SMKN 4 Merangin in 2020 with significant value = 0.000 < 0.05The results showed that there was an increase in knowledge before and after reproductive health education. Therefore, the school can conduct education at least once a month to increase the knowledge of adolescents, especially about adolescent reproductive health problems.Keywords                     : Reproductive Health, KnowledgeReference                    : 33 (2009-2020)